2006
DOI: 10.1021/jf051206s
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Volatile Concentrations in Hand-Squeezed Juices of Four Different Lemon Varieties

Abstract: Fresh juices of four Italian cultivars of lemons (Citrus limon Burm) have been analyzed by headspace solid phase microextraction coupled to gas chromatography and gas chromatography-mass spectrometry (GC-MS). The best results have been obtained with the 2 cm 50/30 microm divinylbenzene/carboxen on poly(dimethylsiloxane) fiber, using a homogenization time of 1 h at 40 degrees C and a sampling period of 30 min. A total of 35 volatile compounds have been identified by GC-MS, and their relative amounts have been c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
35
0
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(43 citation statements)
references
References 15 publications
6
35
0
2
Order By: Relevance
“…Compared to other lemon juice, more abundant volatile compounds were detected in this Eureka lemon (Allegrone et al 2006). The amount of these compounds in free forms was remarkably higher than those in the bound forms.…”
Section: Resultsmentioning
confidence: 63%
See 2 more Smart Citations
“…Compared to other lemon juice, more abundant volatile compounds were detected in this Eureka lemon (Allegrone et al 2006). The amount of these compounds in free forms was remarkably higher than those in the bound forms.…”
Section: Resultsmentioning
confidence: 63%
“…Volatile compounds in Meyer lemon (Moshonas et al, 1972), Italian lemon (Allegrone et al, 2006) and petitgrain Eureka lemon essential oil (Baaliouamer et al, 1985) have been reported, except Eureka lemon. Many studies showed the common volatile compounds in lemon.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some among them, sour citrus fruits such as lemon and lime, are widely known. 1,2) On the other hand, Citrus junos Tanaka (Yuzu), Citrus sphaerocarpa Tanaka (Kabosu), and Citrus sudachi Hort. ex Shirai (Sudachi) are popular in Japan, and there is a custom of squeezing sour citrus juices on grilled fish and on foods served in the pot.…”
mentioning
confidence: 99%
“…Ketones, esters, and alcohols were also found in the samples but at low concentrations (in all cases below 1%). Of note, the composition of the volatile fraction of citrus fibre is qualitatively comparable to those of raw fruits, essential oils [20], and juices [21][22][23].…”
Section: Volatile Composition Of Citrus Fibresmentioning
confidence: 77%